Increased Functionality Through Surface Grafting: Polymeric Surfaces - Cloete, William J.; Klumperman, Bert; Cloete, Thomas E. (Current Organic Chemistry, 2017)
This chapter will give a brief outline on recent advances in grafting techniques for the surface modification of membranes made from synthetic materials or biopolymers, specifically cellulose. In addition, it highlights how these techniques may lead to polymeric surfaces with increased functionality by providing examples where various grafting techniques are used to change the nature of surfaces.
Keywords: Membrane